Cloning of acetyl-CoA acetyltransferase gene from Halomonas elongata BK-AG18 and in silico analysis of its gene product - Ni Putu Yuliastri; Enny Ratnaningsih; Rukman Hertadi (Indonesian Journal of Biotechnology, 2017)
Polyhydroxybutyrate (PHB) is a biodegradable polymer that can be used as a substitute for petrochemical plastics. Bacteria accumulate PHB in their cells as carbon and energy reserves because of unbalanced growth conditions.  This study aimed to amplify phbA from the chromosomal DNA of Halomonas elongata BK-AG18, a PHB-producing bacterium that was previously isolated from the Bledug Kuwu mud crater of Central Java, Indonesia. The obtained phbA amplicon was 1176 bp. This fragment was cloned into a pGEM-T Easy cloning vector and used to transform Eschericia coli TOP10. The recombinant colonies were selected using blue-white screening, confirmed by size screening, reconfirmed by re-PCR, and sequenced. When putative phbA sequences were aligned with H. elongata DSM2581 chromosome using BLASTN, this sequence showed 99% identity. The deduced amino acid sequences of this clone showed 100% identity to PhbA of  H. elongata DSM2581, suggesting that the obtained cloned fragment is a  phbA  gene. The 3D structure predicted by I-TASSER showed that PhbA of H. elongata  BK-AG18 had a high similarity to the acetyl CoA acetyltransferase structure of  Ralstonia eutropha H16. PhbA of H. elongata BK-AG18 possesses three catalytic residues, namely Cys88, His348, and Cys378.